Development of a Higher-Order Thinking Skills (HOTS) Test Instrument on Electrochemical Material for High School Students - Nugrahnastiti, Nuzulul; Kamaludin, Agus (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to develop a HOTS test instrument on electrochemistry topics that meets valid and reliable criteria. Apart from that, the level of difficulty, distinguishing power, ability level, and detection of respondent bias were also analyzed. This research is development research using the Tessmer model, which includes preliminary and formative evaluation stages. The HOTS questions consist of 15 multiple-choice questions. The validation data from experts is measured using a Likert scale. Coefficient Aikens’ V is then used to measure the validation data from reviewers. Experts and reviewer assessments indicated that the HOTS question instrument developed was very good. Analysis of questions using the Rasch model in a field testing of 33 high school students using a purposive sampling technique resulted in 14 valid questions and 1 invalid question with a reliability value of 0,69. There were 3 questions in the easy category, 7 in the moderate category, 1 in the hard category, and 4 in the extremely hard category. The analysis of the distinguishing power of the questions obtained 9 questions with very good criteria, 3 questions with good criteria, and 2 with fair criteria. The results of the validity of the students` responses showed that there were 4 invalid responses. The ability level shows that 5 students have high ability, 7 have moderate ability, and 21 have low ability. In conclusion, the developed HOTS test instrument for electrochemical material has a good quality and is suitable for evaluation.